PENCATATAN RESERVASI PADA FRONT OFFICE DEPARTMENT LABERSA GRAND HOTEL and CONVENTION CENTER - Romi Wahdiromodon; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to determine about the procedure for reservations form of Front Office Department at Labersa Grand Hotel and Convention Center Pekanbaru. Reservation form is the process of making a list of guest orders in accordance with existing procedures. Labersa is an abbreviation of